Особливості відбудови МТС Житомирщини в 1943–1945 рр. - Sidorov, Konstantin; Сидоров, Костянтин (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено особливості відбудови машинно-тракторних станцій у Житомирській області впро-довж 1943–1945 рр., висвітлено проблему кадрового забезпечення працівниками МТС та питання професійної підготовки механізаторських кадрів машинно-тракторних станцій у післявоєнний період.This article explores the revival of the setting up and operation of specific machine-tractor stations in Zhytomyr region for 1943-1945. The problems of staffing employees of MTS and the issue of training staff mechanic machine-tractor stations in the postwar period. This time is characterized with setting up special education schools characterized debugging of special education, who conducted training of specialists in agriculture. We analyze the work units and selfless labor of the peasants, who have been an important source for the reconstruction of MTS and collective farms in the postwar period.
Features MTS Reconstruction in Zhytomyr 1943–1945 Eears
Keywords: машинно-тракторна станція (МТС); Житомирська область; матеріально-технічна база; механізаторські кадри; сільське господарство; machine-tractor stations (MTS); Zhytomyr region; physical infrastructure; mechanic footage; agriculture